Review of Input Congestion Estimating Methods in DEA - Mohammad Khodabakhshi; Farhad Hosseinzadeh Lotfi; Kourosh Aryavash (Journal of Applied Mathematics)
Congestion is an economic phenomenon in the production process where excessive amounts of the input cause a reduction of the output. The motivation of this paper is to investigate and compare the methods provided for estimating congestion in the DEA literature.